Manajemen Pembiasaan Santapan Rohani Sebelum Pembelajaran dalam Penguatan Akhlakul Karimah Siswa - Dinda Auliya Safitri; Ririn Isnadia; Halawatul Fitri; Miftahir Rizqa (MANAGIERE: Journal of Islamic Educational Management, 2025)
This study is motivated by the gap between the ideal objectives of Islamic education in fostering noble character and the reality of students’ moral behavior in schools. Pre-lesson spiritual habituation is viewed as a strategic program that requires proper management to ensure its effectiveness and sustainability. This study aims to analyze the management of pre-learning spiritual routines in strengthening students’ noble character, focusing on the functions of planning, organizing, implementing, supervising, and evaluating. This research employs a library research approach by examining books, scholarly articles, and relevant studies, which are analyzed qualitatively. The findings indicate that well-managed spiritual habituation programs contribute to the development of students’ discipline, honesty, responsibility, politeness, emotional intelligence, and social piety. Furthermore, systematic management of spiritual routines supports the establishment of a religious school culture as part of the hidden curriculum. Therefore, the management of pre-lesson spiritual habituation plays a strategic role in strengthening students’ noble character within the framework of Islamic educational management. Penelitian ini dilatarbelakangi oleh adanya kesenjangan antara tujuan ideal pendidikan Islam dalam membentuk akhlakul karimah dengan realitas perilaku siswa di sekolah. Pembiasaan santapan rohani sebelum pembelajaran dipandang sebagai program strategis yang memerlukan pengelolaan manajerial agar berjalan efektif dan berkelanjutan. Penelitian ini bertujuan menganalisis manajemen pembiasaan santapan rohani sebelum pembelajaran dalam penguatan akhlakul karimah siswa, ditinjau dari fungsi perencanaan, pengorganisasian, pelaksanaan, pengawasan, dan evaluasi. Penelitian ini menggunakan pendekatan penelitian kepustakaan (library research) dengan mengkaji buku, artikel ilmiah, dan hasil penelitian relevan yang dianalisis secara kualitatif. Hasil kajian menunjukkan bahwa pengelolaan santapan rohani yang terencana, terstruktur, dan diawasi secara sistematis berkontribusi pada penguatan kedisiplinan, kejujuran, tanggung jawab, sopan santun, kecerdasan emosional, serta kesalehan sosial siswa. Selain itu, manajemen pembiasaan ini berperan dalam membangun budaya religius sekolah sebagai bagian dari kurikulum tersembunyi. Dengan demikian, santapan rohani yang dikelola secara manajerial menjadi instrumen strategis dalam penguatan akhlakul karimah siswa di sekolah.